Clinically Significant Drug Interactions Between Psychotropic Agents and Repurposed COVID-19 Therapies - Gatti, Milo (CNS Drugs, 2021)
As many patients with underlying psychiatric disorders may be infected with COVID-19, and COVID-19-affected subjects may frequently experience a new onset of psychiatric manifestations, concomitant use of psychotropic medications and COVID-19 therapies is expected to be highly likely and raises concerns of clinically relevant drug interactions. In this setting, four major mechanisms responsible for drug interactions involving psychotropic agents and COVID-19 therapies may be identified: (1) pharmacokinetic drug–drug interactions mainly acting on cytochrome P450; (2) pharmacodynamic drug–drug interactions resulting in additive or synergistic toxicity; (3) drug–disease interactions according to stage and severity of the disease; and (4) pharmacogenetic issues associated with polymorphisms of cytochrome P450 isoenzymes. In this review, we summarise the available literature on relevant drug interactions between psychotropic agents and COVID-19 therapies, providing practical clinical recommendations and potential management strategies according to severity of illness and clinical scenario. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40263-021-00811-2.